Adoption Reasons for Enterprise Systems as a Service - Johansson, Björn (2018)
In 2003 the concept of Application Service Provision (ASP) as a way to provide Enterprise Systems (ES) to Small and Medium sized Enterprises (SMEs), "hyped". In 2013 we saw the same "hype" but now with the Software as a Service (SaaS) model. Even if labelled differently, these concepts seem to mean the same and so, in this paper, we explore if providers perspective for the adoption of external provision of ES as services has changed and, if so, which changes could be seen between the two studies conducted in 2003 (an ASP study) and 2013 (a SaaS study). The main question this paper addresses is: Which changes can be seen from the provider of ES as services point of view as influential reasons to the decision for adopting such services. From the analysis of the two studies, the main conclusion is that providers still emphasize cost as an important factor for adoption, but, there was a change from "having cost control" to "decreasing actual cost".